10w-11-4w=43

Simple and best practice solution for 10w-11-4w=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10w-11-4w=43 equation:


Simplifying
10w + -11 + -4w = 43

Reorder the terms:
-11 + 10w + -4w = 43

Combine like terms: 10w + -4w = 6w
-11 + 6w = 43

Solving
-11 + 6w = 43

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 6w = 43 + 11

Combine like terms: -11 + 11 = 0
0 + 6w = 43 + 11
6w = 43 + 11

Combine like terms: 43 + 11 = 54
6w = 54

Divide each side by '6'.
w = 9

Simplifying
w = 9

See similar equations:

| 52=23t-3y+2 | | 4(n-7)=10n+2 | | 2(5)+10+g=92 | | 8y-6x=3 | | 14x+17+19x=-15 | | w-6+7w=42 | | x+5/12=7/6+x-8/2 | | 9w+6-5w=18 | | x/4=1x/6 | | 7/10=x/25 | | 5(x+3)=-3 | | 29x+33+14x=1 | | 4w-16+w=9 | | 10x-5x=30 | | -2h-3j-4k-2h-3j-4k= | | x+6/6=4/3+x-9/2 | | 5r+1=3r+9 | | 25x+13-33x=11 | | -6r-11r+4=-47 | | 4x+11=10x-1 | | 2x/5-x=x/15-4/3 | | 3x-3=-4x+32 | | 7x/11=5x/9+8 | | 3(v-3)-8v=1 | | 72=27+5x | | 18=-16t^2+35t-5.5 | | 4x^3-11x+5=0 | | 6(u+3)-8u=12 | | x(x+5)=20 | | -32=-6y+2(y-4) | | 8+40.8t-16t^2=10 | | -32=-6+2y(y-4) |

Equations solver categories